2012
DOI: 10.1080/02755947.2012.734895
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Detection Efficiency among Three Sizes of Half‐Duplex Passive Integrated Transponders Using Manual Tracking and Fixed Antenna Arrays

Abstract: We compared detection efficiency for three lengths (12, 23 and 32 mm) of half‐duplex (HDX) passive integrated transponder (PIT) tags for both manual tracking and fixed array applications. In a stream we used a wand‐type manual tracking antenna and determined that detection efficiency was considerably influenced by tag size (i.e., 20% for 12 mm, 43% for 23 mm, and 81% for 32 mm) and water depth. Vertical and horizontal read range also varied among tag sizes (lower for smaller tags) and orientation (12‐mm and 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 33 publications
(68 reference statements)
0
43
1
Order By: Relevance
“…Currently, commercially available PIT tags typically vary in length from 11 to 32 mm. Smaller tags generally have a lower detection range than larger ones when energized by external antennae via an electromagnetic signal [7]. As a consequence, the use of smaller transponder tags (for example, 11 to 12 mm) has largely been restricted to laboratory applications and field studies in systems with water depths less than 40 cm [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, commercially available PIT tags typically vary in length from 11 to 32 mm. Smaller tags generally have a lower detection range than larger ones when energized by external antennae via an electromagnetic signal [7]. As a consequence, the use of smaller transponder tags (for example, 11 to 12 mm) has largely been restricted to laboratory applications and field studies in systems with water depths less than 40 cm [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…each antenna was scanned 2.5 times s −1 ) and upon positive detection stored a unique tag identification number, antenna number and the date and time of detection to the nearest second. Detection efficiency of the system was 97±1.5% for 32 mm tags, based on a separate study undertaken at this site (Burnett et al, 2013). Sturgeon were released into the entrance basin of the fishway immediately following tag attachment and in three separate groups to minimise the number of sturgeon in the fishway at any time whilst maintaining adequate sample sizes.…”
Section: Materials and Methods Study Sitementioning
confidence: 99%
“…The disadvantage is the short detection distance of the readers (<1 m). PIT-tags are frequently used in tagging and recapture studies , and the tag ID can be identified using a hand held reader (Burnett et al, 2013). Automatic stations with tubular or square shaped antennas, or flat-bed antennas, can be installed at suitable sites in small rivers and in fish passes to detect PIT-tagged fish passing the station (Lucas et al, 1999;Aarestrup et al, 2003).…”
Section: Passive Integrated Transponder Tags (Pit-tags)mentioning
confidence: 99%